Prevalence of Anemia among Pregnant Women Attending Primary Health Care Center in Bab-Al-Moudham - Hussein, Athraa karim; Niazy, Shatha Mahmood; Rashid, Buthaina Ateyah; yaqcoob, Ban yousuf; abdul-Razzak, Abeer; Ahmed, Maithem Nasser (Diyala Journal of Medicine, 2019)
Background: Anemia is define as decreased hemoglobin level, or circulating red blood cells and it is the most common hematological disorder during pregnancy. Objective(s): To identify prevalence of anemia, risk factors that contribute to the occurrence of anemia, and to explain the main types of anemia during pregnancy. Materials and methods: A descriptive cross- sectional study conducted at primary health care in Bab- Al-Moudham center in Baghdad city, the sample was selected by non- probability (convenient sampling) and sample size (150). The study started from 1nd March to 10th June 2012, the data was collected by direct interview technique. Previous questionnaire was structured by the researchers to measure the variable of the study; these information infants include (age, educational level, number of children, type of delivery, and type of feeding, .etc). Results: The results shows that most frequent age group was (2-29) years, (34.7%) of mothers were primary school graduate and about (54%) of the pregnant women with anemia had no abortion and no bleeding. Conclusions: The study concluded that higher percentage of pregnant mothers was low rate hemoglobin. Recommendations: The study recommended that encourage pregnant mothers to visit primary health care centers early and regularly and take drugs that prevent the occurrence of anemia during pregnancy period.